Operation witness protection - Davis, Justine (Davis, Justine. Cutter's code., 2023)
Case McMillan isn't a cop anymore, but instinct sends him running when he sees a woman being held at gunpoint. Skittish and secretive, Terri is hard to trust -- until a wily dog named Cutter helps Case see the true self she's been hiding. As the sole witness to a murder, she needs more protection than he alone can provide, but he's not leaving her side until he knows that she's safe.